Improved kinetic model for the transcutaneous measurement of glomerular filtration rate in experimental animals - Friedemann, Jochen; Rädle, Matthias (Kidney international, 2016)
Transcutaneous measurement of the glomerular filtration rate (tGFR) is now frequently used in animal studies. tGFR allows consecutive measurements on the same animal, including multiple measurements on a daily basis, because no blood sampling is required. Here we derive and validate a novel kinetic model for the description of transcutaneously measured FITC-Sinistrin excretion kinetics. In contrast to standard 1- to 3-compartment models, our model covers the complete kinetic, including injection and distribution of the tracer in the plasma compartment. Because the model describes the complete progression of the measurement, it allows further refinement by correcting for baseline shifts observed occasionally during measurement. Possible reasons for shifts in the background signal include photo bleaching of the skin, autofluorescence, changes of physiological state of the animals during the measurements, or effects arising from the attachment of the measurement device. Using the new 3-compartment kinetic model with modulated baseline (tGFR3cp.b.m), tGFR measurements in rats can reach comparable precision as those from GFR measurements assessed using a gold standard technique based on constant infusion of a tracer. Moreover, the variability of simultaneous (parallel) measurements, as well as repeated tGFR measurements in the same animals, showed higher precision when tGFR3cp.b.m was compared with the 1-compartment tGFR1cp model.